2009
DOI: 10.1016/j.cmet.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Imprinting of the G Protein Gsα and Its Role in Metabolic Regulation

Abstract: Summary Albright hereditary osteodystrophy is a monogenic obesity disorder due to heterozygous mutations of Gsα, the G protein which mediates receptor-stimulated cAMP generation, in which obesity only develops when the mutation is on the maternal allele. Likewise, mice with maternal (but not paternal) germline Gsα mutation develop obesity, insulin resistance, and diabetes. These parent-of-origin effects are due to Gsα imprinting with preferential expression from the maternal allele in some tissues. As Gsα is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
150
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 38 publications
22
150
6
1
Order By: Relevance
“…Animal studies have shown that brain-specific maternal Gsα mutation leads to obesity, severe insulin resistance, and diabetes (Chen et al 2009b). Especially, these mice developed insulin-resistant diabetes before the development of obesity, indicating that central Gsα signaling directly regulates peripheral glucose metabolism.…”
Section: Camp/pka In the Brainmentioning
confidence: 99%
“…Animal studies have shown that brain-specific maternal Gsα mutation leads to obesity, severe insulin resistance, and diabetes (Chen et al 2009b). Especially, these mice developed insulin-resistant diabetes before the development of obesity, indicating that central Gsα signaling directly regulates peripheral glucose metabolism.…”
Section: Camp/pka In the Brainmentioning
confidence: 99%
“…However, a causative role for cAMP in MC4R signaling that leads to satiety has not to our knowledge been demonstrated. Indeed, loss of G␣ s function in PVN does not influence feeding behavior (23,24). Thus, the mechanism that links MC4R signaling to changes in neuronal firing, and particularly to the control of feeding behavior, remains unknown.…”
Section: Camentioning
confidence: 99%
“…PHP1a patients also develop obesity (Long et al 2007) but, since GNAS expression is not imprinted in adult adipose tissue (Mantovani et al 2004, Chen et al 2010, Gsa function in adipocytes is not a major contributor to this metabolic phenotype, despite the key role of Gsa in regulating lipid mobilisation. Instead, evidence from tissue-specific ablation of Gnas in mouse implicates imprinted expression in the hypothalamus as the cause (Chen et al 2009). …”
Section: Imprinted Gene Disorders With a Neuroendocrine Involvementmentioning
confidence: 99%